Occurrence and management of resistant weed species in FGV plantation in Malaysia : a review. - Kamalul Adham, Che Ruzlan; Muhammad Saiful, Ahmad Hamdani (Plant Archives, 2020)
Oil palm, currently the world's main vegetable oil crop, is characterized by a large productivity and a long-life span (≥25 years). Weeds are the unwanted plants that grow aggressively, restrict sunlight and compete with desirable plants for nutrients. Weeds population is mainly a mixture of grasses, sedges, broad-leaved weeds plants and ferns in oil palm plantation management. Asystasia gangetica(creeping broad leaf weed), Clidermia hirta (upright woody weed) and Dicranopteris linearis (fern) are amongst noxious weeds under the "must be eradicated "list because of their high tendency to aggressively absorb nutrients and water. In Malaysia alone, since 2004, the use of herbicides has been 67.49% of the total pesticides used. The application of herbicides (e.g. glyphosate, glufosinate, metsulfuron methyl and the recently banned paraquat) in plantations is a common practice even though farmers understand that they are harmful to both applicators and crops if not carefully used. Understanding the mode of herbicidal action is also very useful when diagnosing symptoms of herbicide injuries and to reduce the risk of resistance development in weed populations. Resistance frequently occurs with herbicides that come with very great efficacy to specific weed species, be it acute kill or chronic/slow effect. Herbicide resistance phenomenon in weeds is very depending on the type of herbicides being used (mode of action and selectivity), the period they have been used for, spray dose of the herbicides, the residual effect of the herbicides, the biology and genetic of the weed species being targeted, and existence of other crop management practices that farmers employ. Therefore, weed resistance in Malaysian oil palm plantation is crucial and must be handle with care to avoid unnecessary effect from herbicide resistance.